Regulation and Function of the cGAS-STING Pathway: Mechanisms, Post-Translational Modifications, and Therapeutic Potential in Immunotherapy - Chen Y; Yue S; Yu L; Cao J; Liu Y; Deng A; Lu Y; Yang J; Li H; Du J; Xia J; Li Y; et al. (Drug Design, Development and Therapy)
Yuhan Chen,1,* Si Yue,1,* Lingyan Yu,1,* Jinghao Cao,1 Yingchao Liu,1 Aoli Deng,1 Yajuan Lu,1 Jing Yang,1 Huanjuan Li,1 Jing Du,1 Jun Xia,1 Yanchun Li,2 Yongming Xia3 1Laboratory Medicine Center, Department of Clinical Laboratory, Zhejiang Provincial People’s Hospital (Affiliated People’s Hospital), Hangzhou Medical College, Hangzhou, Zhejiang, People’s Republic of China; 2Department of Clinical Laboratory, Affiliated Hangzhou First People’s Hospital, School of Medicine, Westlake University, Hangzhou, Zhejiang, People’s Republic of China; 3Department of Hematology, Yuyao People’s Hospital, Yuyao, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Xia, Email andisky_005@126.com Yongming Xia, Email xym20246@163.comAbstract: Autoimmune diseases arise when the immune system attacks healthy tissues, losing tolerance for self-tissues. Normally, the immune system recognizes and defends against pathogens like bacteria and viruses. The cGAS-STING pathway, activated by pattern-recognition receptors (PRRs), plays a key role in autoimmune responses. The cGAS protein senses pathogenic DNA and synthesizes cGAMP, which induces conformational changes in STING, activating kinases IKK and TBK1 and leading to the expression of interferon genes or inflammatory mediators. This pathway is crucial in immunotherapy, activating innate immunity, enhancing antigen presentation, modulating the tumor microenvironment, and integrating into therapeutic strategies. Modulation strategies include small molecule inhibitors, oligonucleotide therapies, protein and antibody therapies, genetic and epigenetic regulation, cytokine and metabolite modulation, and nanoscale delivery systems. Post-translational modifications (PTMs) of the cGAS-STING pathway, such as phosphorylation, acetylation, ubiquitination, methylation, palmitoylation, and glycosylation, fine-tune immune responses by regulating protein activity, stability, localization, and interactions. These modifications are interconnected and collectively influence pathway functionality. We summarize the functions of cGAS-STING and its PTMs in immune and non-immune cells across various diseases, and explore potential clinical applications.Keywords: cGAS, STING, immunity, immunotherapy, post-transcriptional regulation